(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This study explores the effectiveness of the shadowing technique in improving English speaking skills among intermediate-level learners. Shadowing, which involves immediate repetition of a model speaker’s speech, was applied over four weeks to assess its impact on fluency, pronunciation, and confidence. A quasi-experimental design was used with 30 participants divided into experimental and control groups.